Revealing the Cape Verde Hotspot Track Across the Great Lakes - Zhongmin Tao; Aibing Li; Jonny Wu; Karen M. Fischer (Geophysical Research Letters)
Abstract Detecting old hotspot tracks in a stable continent remains challenging because of the lack of volcano chains on the surface and the fade of thermal anomalies with time. The northeastern American continent moved over the Cape Verde and the Great Meteor hotspots during 300–100 Ma. However, only the latter was confirmed by kimberlites and seismic velocity models. Our new 3D anisotropic model in northeastern America reveals strong positive radial anisotropy anomalies in the eastern Great Lakes, central Pennsylvania, and northwestern Virginia. These anomalies follow the Cape Verde hotspot track, providing the first geophysical evidence for the hotspot. A circular pattern of azimuthal anisotropy is also observed in the eastern Great Lakes and may be related to the Cape Verde plume activity. The plume was under the Great Lakes during 300–200 Ma and probably caused lithosphere thinning and low topography needed for forming the Lakes during the glacial era.